2004
DOI: 10.1002/bit.20272
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of GS‐NS0 murine myeloma cell lines with varying recombinant monoclonal antibody production rate

Abstract: We have employed an inverse engineering strategy based on quantitative proteome analysis to identify changes in intracellular protein abundance that correlate with increased specific recombinant monoclonal antibody production (qMab) by engineered murine myeloma (NS0) cells. Four homogeneous NS0 cell lines differing in qMab were isolated from a pool of primary transfectants. The proteome of each stably transfected cell line was analyzed at mid-exponential growth phase by two-dimensional gel electrophoresis (2D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 63 publications
(70 reference statements)
3
135
0
Order By: Relevance
“…Factors such as nutritional status may also play a role and are discussed later. Note that, other studies have also observed a positive correlation of mRNA levels of chaperones GRP78, GRP94 and CRT and XBP1 S with that of secreted antibody concentration in production clones (Smales et al 2004;Kober et al 2012).…”
Section: Discussionmentioning
confidence: 54%
“…Factors such as nutritional status may also play a role and are discussed later. Note that, other studies have also observed a positive correlation of mRNA levels of chaperones GRP78, GRP94 and CRT and XBP1 S with that of secreted antibody concentration in production clones (Smales et al 2004;Kober et al 2012).…”
Section: Discussionmentioning
confidence: 54%
“…Overall, the focus on fold changes distracts attention from changes in gene expression that are regulated at a more physiologic scale such as for instance transcription factors that have an effect on the cell upon slight changes in their expression [30]: if within a pathway each individual gene is upregulated 1.4-fold, none of these will show up in the list of differentially expressed genes when using a threshold of 1.5, however, the overall flux through the pathway will increase significantly. [7,66,69,70] Down regulation of growth [7,32,66,68] In case of antibodies: enhanced [4,69,71,[76][77][78]] assembly and secretion due to a surplus of light chain over heavy chain These challenges in identifying relevant genes and understanding their biological roles are further compounded by the fact that many genes have functional assignments in the GO or KEGG annotation databases that reflect the context in which they were first discovered, which may be completely irrelevant to cells grown in suspension in a protein free medium (such as organism development, tissue specific functions and similar). Moreover, pleiotropy, the phenomenon where a single gene may have multiple functions, which may not all be known [31], can make the interpretation of results difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies comparing the HCP proteomes from different production cell lines using the same platform have been reported. These studies showed that the HCP proteomes are very similar among the cell lines evaluated, providing the basis for the platform-based approach for HCP evaluation (Champion et al, 2001;Krawitz et al, 2006;Smales et al, 2004). The second more practical reason, to take the platform approach is the high attrition rate of early drug candidates.…”
Section: Platform-based Approach For Hcp Analysismentioning
confidence: 94%
“…Many studies have been carried out in the application of proteomics for HCP analysis (Dyk et al, 2003;Hayduk et al, 2004;Krawitz et al, 2006;Smales et al, 2004). Krawitz et al (2006) demonstrated using 2D gels that it is possible to establish the comparability of HCPs from different biologics expressed in the same cell line, providing the basis for the platform-based HCP approach.…”
Section: Proteomics Applicationmentioning
confidence: 99%